2018
DOI: 10.1016/j.resp.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary breath-holding duration in healthy subjects with obesity: Role of peripheral chemosensitivity to carbon dioxide

Abstract: The sensitivity of peripheral chemoreflex to CO was preserved in healthy men with obesity. The higher sensitivity of peripheral chemoreflex to CO and higher WHR were associated with a decrease in the duration of voluntary apnea in subjects with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…• From these regression models we calculated both unadjusted and adjusted estimates of the association between the independent and dependent variables. Based on literature review [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] we controlled for and included the following variables in the adjusted models: age (≥50 vs. <50), sex (male vs. female), race (Black/African-American vs. all others), obesity (BMI ≥30 vs. <30), current smoking status (yes/no), history of asthma (yes/no), history of COPD (yes/no), history of congestive heart failure (yes/no), history of hypertension (yes/no), history of type 2 diabetes (yes/no), maximal breath hold time (seconds), baseline desaturation (<95% vs. ≥95%), and whether the subject was on nasal cannula oxygen at the time of conducting the study (yes/no). T-tests (continuous variables) and Fisher's exact tests (categorical variables) were used to compare the baseline characteristics of COVID-19 and healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• From these regression models we calculated both unadjusted and adjusted estimates of the association between the independent and dependent variables. Based on literature review [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] we controlled for and included the following variables in the adjusted models: age (≥50 vs. <50), sex (male vs. female), race (Black/African-American vs. all others), obesity (BMI ≥30 vs. <30), current smoking status (yes/no), history of asthma (yes/no), history of COPD (yes/no), history of congestive heart failure (yes/no), history of hypertension (yes/no), history of type 2 diabetes (yes/no), maximal breath hold time (seconds), baseline desaturation (<95% vs. ≥95%), and whether the subject was on nasal cannula oxygen at the time of conducting the study (yes/no). T-tests (continuous variables) and Fisher's exact tests (categorical variables) were used to compare the baseline characteristics of COVID-19 and healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the early months of the pandemic caused by the severe acute respiratory syndrome coronavirus 2 associated disease (COVID- 19), there were clinical reports of patients with COVID-19 who did not exhibit dyspnea [1], despite having hypoxemia and evidence of impaired pulmonary gas exchange [2]. This phenomenon was described as "happy" or "silent hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…2). Studies on mechanism of cortical control of ventilation showed that the duration of breath-holding can be limited by several factors, such as sensitivity of peripheral chemoreflex, spirometry parameters, the arterial PCo 2 , PO 2, previous maneuver (Bain et al, 2017;Trembach & Zabolotskikh, 2018).Ventilatory response to PCo 2 and PO 2 is considerably variable between patient (West & Luks, 2016).The duration of voluntary breath-holding doubled after breathing a hyperoxic mixture or after pre-hyperventilation. Those whose minimum post breath-holding SaO 2 was lower, might have a higher likelihood of changing CPAP to BiPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Such responses appear to be independent of the effects of obesity as well 19 . Central chemoreceptor activation elicited by hypercapnia is accentuated in those with obesity (although not all reports are consistent), whereas it is mainly the peripheral chemoreceptor response to hypoxemia that is enhanced in subjects with OSA 47,54,55 . Resting muscle sympathetic nerve activity, measured during normal awake normoxic breathing, is higher in subjects with OSA compared to obese controls 56,57 .…”
Section: Nrem Sleepmentioning
confidence: 97%